2018
DOI: 10.3389/fpsyg.2018.02207
|View full text |Cite
|
Sign up to set email alerts
|

The Destructive Effect of Ingroup Competition on Ingroup Favoritism

Abstract: Ingroup favoritism has been widely verified in the context of intergroup competition; however, how competition among ingroup members affects ingroup favoritism remains unclear. We hypothesized that competition among ingroup members may disrupt individuals’ ingroup-favoring behavior because of conflicts of interest; we tested this hypothesis in two studies. In Study 1, we manipulated competitive intragroup outcome interdependence (present vs. absent) and the manner in which results were presented (public vs. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(54 reference statements)
2
9
1
Order By: Relevance
“…These results directly replicated the results of previous studies in which the Chinese participants were also found to be more inclined to cooperate with outgroup members under the minimal group paradigm (Wu et al, 2015, 2016). Similar results were also reported by researches using other tasks under minimal group paradigm (Zuo et al, 2018; Dang et al, 2019). For example, researchers found that East Asian participants allocated more resources to the outgroup members than to ingroup members when there were intragroup competitions within the minimal groups (Zuo et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results directly replicated the results of previous studies in which the Chinese participants were also found to be more inclined to cooperate with outgroup members under the minimal group paradigm (Wu et al, 2015, 2016). Similar results were also reported by researches using other tasks under minimal group paradigm (Zuo et al, 2018; Dang et al, 2019). For example, researchers found that East Asian participants allocated more resources to the outgroup members than to ingroup members when there were intragroup competitions within the minimal groups (Zuo et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…As a wide-accepted paradigm to study intergroup bias in the laboratory, the minimal group paradigm categorizes people into arbitrary social categories or groups, such as whether they have a “red” personality type or a “green” personality type based on bogus personality tests, which provides group-categorization heuristics to one’s actual social group membership (Tajfel et al, 1971; Brewer, 1979; Bernstein et al, 2007; Paladino and Castelli, 2008; Makhanova et al, 2015; Wu et al, 2015, 2016). Studies employing this paradigm have shown strong cognitive, motivational, and behavioral differences in responses to these arbitrarily constructed ingroups and outgroups, 2 which were very similar to the responses elicited by actual social groups (e.g., Tajfel et al, 1971; Brewer, 1979; Bernstein et al, 2007; Paladino and Castelli, 2008; Makhanova et al, 2015; Wu et al, 2015, 2016; Zuo et al, 2018; Dang et al, 2019). Therefore, following the studies of Wu et al (2015) and Wu et al (2016), we also employed the minimal group paradigm to elicit the ingroup derogation phenomenon.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations